Pengaruh Kebijakan Dividen, Leverage dan Profitabilitas terhadap Nilai Perusahaan LQ-45 yang Terdaftar di Bursa Efek Indonesia - Gisa Anugrah Dessriadi; Harsuti Harsuti; Siti Muntahanah; Tjahjani Murdijaningsih (Universitas Batanghari Jambi, 2022)
The aim of this research was to find out and analyze the significant effect of dividend policy, leverage, and profitability on firm value of LQ-45 companies listed on Indonesia Stock Exchange year of 2015 until 2019. Type of this research was quantitative with method of data analysis used panel data regression. The research results showed that dividend policy, leverage as well as profitability has a positive and significant effect on firm value of LQ-45 companies listed on Indonesia Stock Exchange year of 2015-2019. Referred to the conclusion, management of LQ-45 companies listed on Indonesia Stock Exchange needs to prioritize their financial policies related to dividend policy, leverage and profitability. The ways could be done by continue to pay or distribute dividend regularly every year while still managing retained earnings effectively, set a proportional debt level and controlling the operational costs more efficiently as well as continuously increase their capital investment or productive investment as an effort to optimize the company's ability to earn profits.